DAYA TAMPUNG SETTLING POND TERHADAP BEBAN PENCEMARAN TOTAL SUSPENDED SOLID DARI LIMBAH BATUBARA PT. JORONG BARUTAMA GRESTON - Tresnawati, Nina; Asmawi, Suhaili; Kissinger, Kissinger; Fauzana, Noor Arida (EnviroScienteae, 2024)
The impact of the mining process including the emergence of Total Suspended Solids (TSS), either directly or indirectly can disrupt the life of aquatic biota, damage environmental sustainability, and threaten the welfare of humans who depend on the water for various daily purposes. To reduce the burden of pollution on water bodies due to coal mining waste, one of the technologies often chosen is the Wastewater Management Plant (WWTP) system, which generally involves the use of settling ponds. This study aims to analyze the total suspended solids in the settling pond, analyze the total suspended solid capacity, and compile recommendations for total suspended solid management efforts to meet environmental quality standards. The total suspended solids (TSS) values in October and November measurements at the inlet were 339.00 mg/l and 712.00 mg/l while the outlet decreased to 42.50 mg/l and 55.00 mg/l. The total suspended solid (TSS) value during the measurement period of January – December 2023 shows that the TSS value at the inlet and outlet for 12 months shows a value below the quality standard. The first settling pond with a capacity of 15,000 m, and the second to sixth settling ponds have a capacity of 3,000 m3  each. To maintain the capacity of the settling pond at around 60% of its maximum capacity, the volume of TSS deposited ranges from 9,000 m3, while in the second to sixth settling ponds, the volume of TSS deposited each ranges from 1,800 m3.